2012
DOI: 10.9734/bjast/2012/1078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Chemical Quality of Potable Water Sources in Abuja, Nigeria

Abstract: Author MMA collected water samples for laboratory analysis and also designed the study, in addition to providing overall direction for the work. Author FU managed the literature review, performed the statistical analysis, and wrote the first draft of the manuscript. All Authors read and approved the final manuscript before submission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Going by this standard, 44(88%) of the samples exceeded the MCL for nitrate. In drinking water, a nitrate level of up to 3 mg/l is generally believed to be safe for drinking (Alhassan and Ujoh, 2012). Regulation of drinking water quality is so important that the United States Congress passed the safe drinking water act in 1974 (Njeze et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Going by this standard, 44(88%) of the samples exceeded the MCL for nitrate. In drinking water, a nitrate level of up to 3 mg/l is generally believed to be safe for drinking (Alhassan and Ujoh, 2012). Regulation of drinking water quality is so important that the United States Congress passed the safe drinking water act in 1974 (Njeze et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also reported high manganese concentrations in PW; A recent Nigerian study found 42.5% of bottled and sachet samples exceeded 0.4 mg/L, with concentrations as high as 12.9 mg/L [ 27 ]. While chronic exposure to high manganese concentrations has been associated with neurological and cognitive impairment, the concentrations reported in this study (< = 0.6 mg/L) probably do not represent a substantial increase in risk relative to the Tolerable Daily Intake of 0.06 mg/kg of body weight established by the WHO [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TC have many non-fecal environmental sources [ 34 ], and E . coli has non-fecal sources as well [ 25 , 27 ]. Nevertheless, most plausible pathways for contamination of PSW by FIB imply increased risk of fecal contamination, suggesting that differences in the prevalence and concentration of E .…”
Section: Discussionmentioning
confidence: 99%
“…3 mg/L is generally believed to be safe for drinking. [4] Regulation of drinking-water quality is so important that the United States Congress passed the safe drinking water act in 1974. This law requires the environmental protection agency (EPA) to determine safe levels of contaminants in water, at which no adverse health effects are likely to occur [12,13] As a consequence of that law, the regulation for nitrate, became effective in 1992 and EPA set the maximum contaminant level (MCL) for nitrate as 10 mg/L (or 10 ppm).…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] High level of nitrate in drinking water can be dangerous to health. [4] A nitrate level of up to 3 ppm i.e., 3 mg/L is generally believed to be naturally occurring and safe for drinking. [5] Beyond this level, contamination is suspected.…”
Section: Introductionmentioning
confidence: 99%